THU0322 Secukinumab provides sustained improvements in the signs and symptoms of active psoriatic arthritis: 3-year results from the phase 3 future 2 study. (12th June 2018) - Nash, P.; McInnes, I.B.; Rahman, P.; Gottlieb, A.B.; Kirkham, B.; Ding, K.; Pricop, L.; ,
Abstract : Background: Secukinumab, a fully human monoclonal antibody that selectively neutralises IL-17A, provided significant and sustained improvement in the signs and symptoms of active psoriatic arthritis (PsA) over 2 years in the FUTURE 2 study (NCT01752634 ). 1 Objectives: To report 3 year efficacy and safety results from the FUTURE 2 study. Methods: Overall, 397 patients (pts) with active PsA were randomised to receive subcutaneous secukinumab (300, 150 or 75 mg) or placebo at baseline, Weeks (Wks) 1, 2, 3 and 4, and every 4 wks thereafter. 1 Assessments at Wk 156 are from pts originally randomised to secukinumab and included ACR20/50, PASI 75, HAQ-DI, and resolution of dactylitis and enthesitis. Analyses by prior anti-TNF use (naïve/inadequate response [IR]) and with/without concomitant methotrexate (MTX) were assessed. Data are reported as observed for secukinumab 300 and 150 mg (approved doses). Safety analysis included all pts who received ≥1 dose of secukinumab. Results: In total, 73/100 (73.0%) and 72/100 (72.0%) pts in the secukinumab 300 and 150 mg groups, respectively, completed 156 wks of treatment. Sustained clinical improvements were observed in those continuing with secukinumab across all endpoints through Wk 156 (table 1). ACR20 response rates at Wk 156 in anti– TNF-naïve pts were 85.2% and 76.5% with secukinumab 300 and 150 mg respectively; corresponding rates in anti– TNF-IR pts were 55.6% and 54.5%. ACR20 response rates in pts receiving concomitant MTX were 73.0% and 77.1% with secukinumab 300 and 150 mg, respectively; rates in pts without concomitant MTX use were 77.3% and 63.2%. Over the study (mean secukinumab exposure of 991.3 days) the type, incidence and severity of adverse events (AEs) were consistent with that reported previously. Exposure adjusted incidence rates with secukinumab for selected AEs of interest were: serious infections (1.8), candida infections (1.8), inflammatory bowel disease (0.1), major adverse cardiovascular event (0.2) and malignant/unspecified tumours (1.2). Conclusions: Secukinumab 300 and 150 mg provided sustained improvements in signs and symptoms of active PsA through 3 years. Secukinumab was well tolerated, with a safety profile consistent with that reported previously. 1 Reference: [1] McInnes IB, et al. Rheumatology (Oxford)2017;56:1993–2003. Acknowledgements: The study was sponsored by Novartis Pharma AG Disclosure of Interest: P. Nash Grant/research support from: Novartis, Abbvie, Roche, Pfizer, BMS, Janssen, and Celgene, Consultant for: Novartis, Abbvie, Roche, Pfizer, BMS, Janssen, and Celgene, I. McInnes Grant/research support from: Abbvie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, and UCB, Consultant for: Abbvie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, and UCB, Speakers bureau: Abbvie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, and UCB, P. Rahman Consultant for: Abbott, Abbvie, Amgen, BMS, Celgene, Janssen, Novartis, Pfizer and Roche and pharmaceutical companies dealing with biologic agents in rheumatology, A. Gottlieb Grant/research support from: Janssen, Incyte, Consultant for: Janssen Inc., Celgene Corp., Bristol Myers Squibb Co., Beiersdorf, Inc., Abbvie, UCB, Novartis, Incyte, Lilly, Reddy Labs, Valeant, Dermira, Allergan, Sun Pharmaceutical Industries, Speakers bureau: Janssen Inc., Celgene Corp., Bristol Myers Squibb Co., Beiersdorf, Inc., Abbvie, UCB, Novartis, Incyte, Lilly, Reddy Labs, Valeant, Dermira, Allergan, Sun Pharmaceutical Industries, B. Kirkham Grant/research support from: Abbvie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Roche, and UCB, Consultant for: Abbvie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Roche, and UCB, Speakers bureau: Abbvie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Roche, and UCB, K. Ding Shareholder of: Novartis, Employee of: Novartis, L. Pricop Shareholder of: Novartis, Employee of: Novartis